PERSEPSI MAHASISWA AKUNTANSI MENGENAI PENGARUH PREVENTING DAN NEUTRALIZATION TERHADAP KECENDERUNGAN BERPERILAKU CURANG (STUDI EMPIRIS PADA UNIVERSITAS ISLAM MALANG) - Ekky Dian Muharromah; Mohammad Amin; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to determine how much effect of preventingand neutralization to accounting students at University Islam of Malang forfraudulently behavior. this research uses purposive sampling technique. Thepopulation of this research are accounting students at University Islam ofMalang. The selected sample results based on predetermined criteria are 160respondents accounting students at University Islam of Malang. An analysis ofdata using analysis regression multiple linier method and using SPSS program.The result of analysis showed that the act of preventing negative and significant tofraudulently behavior in accounting students at University of Islam Malang.While for variable neutralization are positive and significant to fraudulentlybehavior in accounting students at University of Islam Malang.Keywords: preventing, neutralization, and fraudulently behavior.